Simulation for Selecting Road Works Equipment - Jaśkowski, Piotr; Czarnigowska, Agata; Tokarski, Zbigniew; Sobotka, Anna (The Baltic Journal of Road and Bridge Engineering, 2015)
Efficiency of road works is conditioned by selection of machines and synchronizing their operations. Modelling these works using queuing theory allows the planner to conduct an in-depth analysis of the system’s operation to find the best machine types and their optimal number. For simple cases, analytic formulas are used to calculate such parameters as a probability of a server’s standing idle, average length of a queue, or average waiting time. However, complex real-life systems are to be analyzed more efficiently by means of simulations. The paper presents simulation model of a road repaving project. Using it, the authors evaluated the economic effect and output of the system served by different machine sets. Applying a number of additional optimization criteria (cost, productivity, machine utilization rates, etc.) the authors were able to find most suitable machine sets.